Confucian Ethics as a Design Paradigm: Shaping Chinese Architecture in Malaysia for Sustainable Communal Living - ismail, alice (Advances in Humanities and Contemporary Studies, 2025)
The presence of Chinese Malaysian communities in Malaysia had evolved since the Malaccan Sultanate, with the Ming dynasty establishing commercial and diplomatic ties in the 13th century, which later led to the late 19th century under the British colonial rule that formed the new Chinese Malaysian demographic due to the new wave of Chinese immigrants arriving in Malaya for trade and employment opportunities. These communities have developed distinctive cultural practices facilitated by integrating Confucian rituals into everyday life. Their cultural identity combines traditional Chinese and modern cultural features and those of Malaysian origin through an acculturation process, thereby ingraining these values into the fabric of society. Due to their unique cultural practices and customs, where Confucian teaching serves as a framework for conceptualising various aspects of life, including habits, social practices, and the overall ethos of societies grounded in Confucian principles for generations, these Chinese Malaysian communities significantly shaped Malaya's historical and urban landscape identity, including the built environment. Henceforth, this study first aims to identify these Confucian characteristics and analyse to what extent the level of Confucian ethical values influences Chinese Malaysian architecture after acculturation with the local context. The Chinese shophouses, ancestral halls, and clan houses in Malaysia were chosen as they are the most regional architectural type, practical, and rich in Confucian connotation. These prominent  Chinese buildings in Malacca and Penang were selected because they still uphold Malaysia's Confucian principles and value systems. The method used in this study is the qualitative descriptive method, which falls under the interpretive anthropology paradigm, aligning the semiotics and hermeneutics methods to understand the symbolic meaning of the house's architectural elements. The study concludes that there was an acculturation process between the authenticity of Confucian principles and their symbolic value influence on Chinese architecture in Malaysia in terms of architectural form and space-making. In this way, Malaysian Chinese architecture becomes a living embodiment of Confucian values, whether in its original built form or undergoing acculturation. This contributes to a broader understanding of how Confucian ethical values can support a more harmonious and sustainable way of life in contemporary living in multicultural Malaysia.